SYMBOLIC VIOLENCE TOWARDS WOMAN IN CATATAN HATI SEORANG ISTRI - Ardheo Prayitno; Dr. Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Television is a stuff to fulfill entertain and information needs. One of television product called soap opera, but this soap opera often showing restricted show. This soap opera broadcast on prime time, because of violence broadcast in soap opera, this got warning from Komisi Penyiaran Indonesia (KPI) as Indonesian Broadcast Commission. One of their warning is violences in television broadcast. The purpose of this essay is to find violences toward woman in Catatan Hati Seorang Istri and to uncover hidden ideologies in this soap opera. This essay use descriptive qualitative approach with Roland Barthes semiotics analysis by syntagmatic and paradigmatic. In paradigmatic analysis use 5 codes theory from Roland Barthes. There are 8 lexist in this essay, based on those lexist can use to determine the purpose of this essay to determine how this soap opera showed violences toward woman from syntagmatic analysis which form this soap opera (camera, setting, make-up, dialog, and lighting). Based on those 8 lexists, there are violences towards woman in this soap opera, that violences contain verbal, non-verbal, and physical violences. These violences happened because of patriarchy ideology which being main ideology from plot of Catatan Hati Seorang Istri soap opera.